Respuesta :

see the attachments below for the steps :)

The simplified expression is as follows:

d(-3x^2 + 9x - 14)

Ver imagen foreveryoungblood
Ver imagen foreveryoungblood

Answer:

-21

Step-by-step explanation:

The given functions are

[tex]f(x)=3x-4[/tex]

[tex]g(x)=-2x+7[/tex]

We need to find the value of [tex](g\circ f)(6)[/tex].

The substitute x=6 in f(x), to find the value f(6).

[tex]f(6)=3(6)-4=18-4=14[/tex]

The substitute x=14 in g(x), to find the value g(14).

[tex]g(14)=-2(14)+7=-28+7=-21[/tex]

According to the composition of functions,

[tex](g\circ f)(x)=g(f(x))[/tex]

Substitute x=6 in the above formula.

[tex](g\circ f)(6)=g(f(6))[/tex]

[tex](g\circ f)(6)=g(14)[/tex]

[tex](g\circ f)(6)=-21[/tex]

Therefore the value of [tex](g\circ f)(6)[/tex] is -21.

ACCESS MORE